The impact of brand identity in achieving marketing objectives Applied Study in the International Company for smart card "Key Card" - جاسم سرمد حمزة; عبد الحسين سماء علي (Journal of Economics and Administrative Sciences, 2019)
Each organization has values ​​and objectives, tangible and intangible properties of its products. The reflection of properties on the brand constitutes the identity of the brand that contributes to building the customer’s convictions about the products or services provided by any organization and its brand in a positive or negative way. This is reflected in purchasing behavior, which may push forward the progress towards marketing goals or deviation from them. Therefore, the current research came to identify the brand identity, its types and the factors affecting them and how they affect to achieve each of the marketing goals. At a time when the number of brands and varied identities and similar to many times, aking the researcher from the basic research problem of asking how the identity of the mark can contribute to the achievement of marketing goals? In order to identify any marketing objective that contributes to the identity of the mark to achieve more than the other goals, according to the main research hypothesis, "the identity of the brand has a significant impact on the achievement of marketing goals." The managers of the global smart card company in Iraq were chosen 203 managers of the research community and 86 of them were selected for practical applications to test the hypothesis using statistical methods, including the means and standard deviation to measure the homogeneity of the answers to the questions and the simple linear regression test to measure the degree of influence between Variables. The research found that there is a relationship of influence of the brand identity in achieving the marketing objectives. The stronger influence of the brand identity on building customer relations while profit growth was the weakest relationship. The researcher recommended that the company need to formulate clear profit growth policies and inform employees of the profit growth rates to be achieved. It is not necessarily a growth in profits. It is not necessarily a growth in profits. It is an important element in the sustainability of its success.